NLGP Attenuates Murine Melanoma and Carcinoma Metastasis by Modulating Cytotoxic CD8+ T Cells - Bhuniya, Avishek; Guha, Ipsita; Ganguly, Nilanjan; Saha, Akata; Dasgupta, Shayani; Nandi, Partha; Das, Arnab; Ghosh, Sarbari; Ghosh, Tithi; Haque, Enamul; Banerjee, Saptak; Bose, Anamika; et al. (Frontiers in Oncology, 2020)
Neem leaf glycoprotein (NLGP), a natural immunomodulator, attenuates murine carcinoma and melanoma metastasis, independent of primary tumor growth and alterations in basic cellular properties (cell proliferation, cytokine secretion, etc.). Colonization event of invasion-metastasis cascade was primarily inhibited by NLGP, with no effect on metastasis-related invasion, migration and extravasation. High infiltration of IFNγ secreting cytotoxic CD8+ T cells (CD44+, CD69+, GranB+, IFNγ+ and IL-2+) was documented in the metastatic site of NLGP treated mice. Systemic CD8+T cell depletion abolished NLGP mediated metastasis inhibition and reappeared upon adoptive-transfer of NLGP activated CD8+ T cells. CD8+ T cells secreted IFNγ inhibits the expression of angiogenesis regulatory VEGF, TGFβ and have an impact on the prevention of colonization. NLGP modulates dendritic cells (DCs) for proper antigen presentation by it’s DC surface binding and upregulation of MHC-I/II, CD86 and CCR7. NLGP treated DCs specifically imprints CXCR3 and CCR4 homing-receptors on activated CD8+ T cells which helps to infiltrate into metastatic sites to restrain colonization. Such NLGP’s effect on DCs is translation dependent and transcription-independent. Studies using ovalbumin, OVA257-264 and crude B16F10 antigen indicate MHC-I upregulation depends on the quantity of proteasome degradable peptide and only stimulate CD8+ T cells in the presence of antigen. Overall data suggest NLGP inhibits metastasis, in conjunction with tumor growth restriction, thus, might appear as a promising next-generation cancer-immunotherapeutic.